Pliocene to Early Pleistocene Drainage Reorganization in Eastern Tibet Inferred From Detrital Zircons - Xudong Zhao; Huiping Zhang; Yaling Tao; Ying Wang; Jianzhang Pang; Yan Ma; Jiawei Zhang; Zifa Ma; Jianguo Xiong (Geophysical Research Letters)
Abstract The drainage evolution in eastern Tibet during the India‐Eurasia collision has attracted considerable attention because of its critical link to topographic development and plateau growth, but the discussion still persists. In the present study, new and published detrital zircon U‐Pb ages are integrated from Pliocene‐Early Pleistocene Xigeda Formation (XGD) and modern river sands to decipher the paleo‐drainage evolution in eastern Tibet. The results confirm the eastward flow of the Jinsha River before the Pliocene, but the drainage patterns of its major tributaries (Dadu, Yalong, and Anning) in the Pliocene, differ from the modern ones. In conjunction with the previously documented fluvial incision in eastern Tibet, we interpreted that the excavation of the Paleo‐Xigeda lake in Early Pleistocene time initiated and accentuated incision of the Jinsha River and its major tributaries. This led to drainage reorganization and the modern river pattern establishment in eastern Tibet.